Assessment of cochlear electrophysiology in typically developing children and children with auditory processing disorder. (December 2021) - Veeranna, Sangamanatha Ankmnal; Allan, Chris; Allen, Prudence
Abstract: Objective: Children with auditory processing disorder (APD) are reported to have abnormal auditory brainstem responses (ABR) but little is understood about their cochlear integrity. Poor cochlear integrity can affect neural responses. In this study, cochlear and auditory brainstem integrity was investigated in children with APD. Method: Twenty children with APD, sixteen typically developing children and twenty adults participated in this study. Click evoked electrocochleography (ECochG) and ABRs were recorded from all the participants. Cochlear responses were analyzed using a) latency and amplitude of summating potential; action potential, b) transmission time between summating potential and action potential, c) summating potential/action potential amplitude ratio and d) action potential latency difference to condensation and rarefaction polarity. Amplitude in the ABR components was examined. Results: Children with APD showed similar cochlear function to the typically developing children. There were no significant differences in wave I amplitude between children with APD and typically developing children. However, wave V amplitude was significantly reduced in children with APD compared to typically developing children. Conclusion: In the absence of any functional differences in the cochlea, children with APD can show poor amplitude in the later components of the ABR. The ABR anomalies observed in children with APD arise due to poor neural processing, possibly after the first auditory synapse.